Advances in Diagnosis and Treatment of Sexual Dysfunctions in Men: A Comprehensive Review of Late-onset Hypogonadism, Erectile Dysfunction, and Premature Ejaculation - Amiri, Mina; Noroozzadeh, Mahsa; Azizpour, Farhid; Parsa Nik, Tuba; Ramezani Tehrani, Fahimeh (Archives of Men's Health, 2023)
This study aims to describe prevalent male sexual dysfunctions, including late-onset hypogonadism (LOH), erectile dysfunction (ED), and premature ejaculation (PE). We summarize diagnostic evaluation, and current pharmacological approaches, along with international recommendations for managing these disorders. Accurate evaluation using standardized tests with defined thresholds is crucial before initiating treatment for male sexual dysfunction. This review provides a comprehensive overview of standard diagnostic evaluation and treatment of male sexual dysfunctions, with a focus on pharmacological interventions, aiming to a balance between efficacy and safety. While existing literature offers valuable insights, our review underscores the need for precise evaluation before prescribing these medical agents to identify real indications of the treatment. Clinicians should consider individual patient characteristics, potential adverse effects, and evidence-based recommendations when selecting the most appropriate treatment.